Study of direct and indirect exciton states in GaAs-Ga1-xAlxAs quantum dots under the effects of intense laser field and applied electric field (2012)
ABSTRACT: The effects of intense laser radiation on the exciton states in GaAs-Ga1−xAlxAs quantum dots are studied with the inclusion of applied dc electric fields oriented along the growth direction of the system. The calculations are made within the effective mass and parabolic band approximations. The intense laser effects have been included along the lines of the Floquet method, modifying the confinement potential associated to the heterostructure. The laser field modifies the Coulomb potential via the generation of two interaction centers. The exciton binding energy behaves as a decreasing function of the laser field strength, as well as of the size of the quantum dot. The normalized photoluminescence peak energy increases with the laser field strength and behaves as a decreasing function of the dot’s dimensions for fixed laser field intensity.